Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Restrict the domain of $f(x)$ to find inverse:

\begin{align} f(x) & = x^2+6x+9 = (x+3)^2 \\ g(x) & = \sqrt{x} - 3 \end{align}

share|improve this question
    
Welcome to math.SE: since you are new, I wanted to let you know a few things about the site. In order to get the best possible answers, it is helpful if you say in what context you encountered the problem, and what your thoughts on it are; this will prevent people from telling you things you already know, and help them give their answers at the right level. Also, many find the use of imperative ("Prove", "Solve", etc.) to be rude when asking for help; please consider rewriting your post. –  Julian Kuelshammer Dec 18 '12 at 8:30
add comment

1 Answer

The function $f$ is not one-to-one on $\Bbb R$, so in order to find an inverse for $f$, you need to find a subset $D$ of $\Bbb R$ on which $f$ is one-to-one. The graph of $y=(x+3)^2$ is symmetric about the line $x=-3$. This means that values of $x$ equidistant from $-3$ have the same image under $f$: for any $a$,

$$f(-3+a)=\big((-3+a)=3\big)^2=a^2=(-a)^2=\big((-3-a)+3\big)^2=f(-3-a)\;.$$

Thus, $D$ cannot contain both $-3+a$ and $-3-a$ for any $a$. The simplest ways to arrange this are to take $D$ to be either $$[-3,\to)=\{x\in\Bbb R:x\ge -3\}\tag{1}$$ (also written $[-3,\infty)$) or $$(\leftarrow,-3]=\{x\in\Bbb R:x\le -3\}\tag{2}$$ (also written $(-\infty,-3]$).

$$D=[-3,\to)=\{x\in\Bbb R:x\ge -3\}\;.$$

Now go back to $y=(x+3)^2$ and solve for $x$ in terms of $y$: $x+3=\pm\sqrt y$, and $x=\pm\sqrt y-3$. If we choose the positive square root, we get the function $g(x)=\sqrt x-3$; if we choose the negative square root, we get the function $h(x)=-\sqrt x-3$. Each of these is an inverse of $f$ on some domain, and it’s not hard to check that $g$ goes with the domain $(1)$ and $h$ with the domain $(2)$: for any $x\ge 0$, $g(x)=\sqrt x-3\ge-3$ and $h(x)=-\sqrt x-3\le-3$.

In most contexts it’s more natural to choose the function $g$ and the domain $(1)$: the function $g(x)=\sqrt x-3$ is the inverse of the restriction of $f$ to the domain $[-3,\to)$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.